2006
DOI: 10.1021/es051720e
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Degradation Rates of Chlorinated Ethylenes in Column Experiments with Commercial Iron Materials Used in Permeable Reactive Barriers

Abstract: Multiple column experiments were performed using two commercial iron materials to evaluate the necessity and usefulness of preliminary investigations in permeable reactive barrier (PRB) design for chlorinated organics. Experiments were performed with contaminated groundwater and involved fresh iron granules or altered iron material excavated from PRBs. The determination of first-order rate coefficients by global nonlinear least-squares fittings indicated a variability in rate coefficients on 1 or 2 orders of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Columns were run for several days until an apparent steady state was reached, that is, until there was no measurable change in effluent concentrations over time. Previous work has demonstrated that under these conditions, column profiles develop that are consistent with a first-order disappearance of TCE along the column length (Gillham and O'Hannesin 1994;Ebert et al 2006;Plagentz et al 2006). On this basis, sampling was restricted to the effluent and pseudo-first-order kinetics were assumed to apply.…”
Section: Column Preparation and Samplingmentioning
confidence: 73%
“…Columns were run for several days until an apparent steady state was reached, that is, until there was no measurable change in effluent concentrations over time. Previous work has demonstrated that under these conditions, column profiles develop that are consistent with a first-order disappearance of TCE along the column length (Gillham and O'Hannesin 1994;Ebert et al 2006;Plagentz et al 2006). On this basis, sampling was restricted to the effluent and pseudo-first-order kinetics were assumed to apply.…”
Section: Column Preparation and Samplingmentioning
confidence: 73%
“…All solutions receiving ions (except for column S2B) were adjusted to a neutral pH value of 7 by addition of hydrochloric acid; the pH 9 of the feed solution for column S2B was adjusted by addition of potassium hydroxide. Columns were filled with 150 g granulated cast iron (nominal grain size 300-2000 μm, Gotthart Maier, Germany) which has been used in a number of laboratory investigations (Ebert et al, 2006;O et al, 2009;Rosenthal et al, 2004;Van Nooten et al, 2007) and field applications (Birke et al, 2003a(Birke et al, , 2003b. Column S2S (75 g) and column S2L (270 g) contained different amounts for elucidation of the relative influence of column length.…”
Section: Materials Methods and Calculationsmentioning
confidence: 99%
“…This oxidative dissolution process is commonly known as iron corrosion, which is usually mostly a destructive process. However, examples of taking advantage from iron corrosion are also well documented (Noubactep , 2013a ) For example, porous direct reduced iron (sponge iron) has been tested as an alternative to compact Fe 0 material for contaminant removal in passive filters, including Fe 0 permeable reactive barriers (PRBs) during the past two decades (Ebert et al , 2006 ;Li, Li, & Li, 2009;Li, Wei, Li, Bi, & Song, 2011;Schlicker et al , 2000 ;Yi et al , 2013 ). However, sponge iron is a traditional material used as oxygen scavenger in water treatment plants (Li et al , 2011 ;Yi et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%